FACTORS AFFECTED CREATIVE ACCOUNTING PRACTICES IN DEVELOPING COUNTRIES: A COMPARATIVE STUDY BETWEEN INDONESIAN AND MALAYSIAN - Trisanti, Theresia (Fakultas Bisnis UKDW, 2014)
This paper presents the findings of creative accounting practices such as income smoothing practices and to identify factors associated with the incidence of income smoothing practices in Indonesian and Malaysian listed firms. The coefficient of variation method introduced by Eckel‟s (1981) and modified by Atik (2009) was used to determined income smoothing practices. The data used were the financial reports of each sample company which obtained through DataStream from 2009 - 2012. Four hypotheses, which relate income smoothing practices such as company age, company size, profitability and debt financing, are tested in this research. Logistic regression indicated that in Indonesian, company age, profitability, debt financing have positive significant influence to income smoothing practices but company size has negative significant. For Malaysia, company size, company age and profitability are significantly associated with Income smoothing practices but debt financing has negative significant relationship. Keywords: Income Smoothing Practices, Company Age, Company Size, Debt Financing, And Profitability